CARTOGRAFIA DELLA PRATERIA DI POSIDONIA OCEANICA DI BERGEGGI: 35 ANNI DI STORIA - Oprandi, Alice; Fouillet, Lea; Morri, Carla; Bianchi, Carlo Nike; Mancini, Ilaria; Azzola, Annalisa; Robello, Chiara; Montefalcone, Monica (Biologia Marina Mediterranea, 2024)
The study of Posidonia oceanica meadows in the Ligurian Sea dates back to the beginning of the 20th century. The first maps summarising the presence and position of seagrasses along the coast, however, were only produced in the mid-1960s with the aim of indicating the best catch areas for commercial fishing. Detailed thematic mapping aimed at defining the exact extent and distribution of P. oceanica was only developed in the second half of the 1980s. Thematic mapping is a relatively recent survey tool that has proved to be extremely effective for assessing the change in marine ecosystems over time and for their proper management. P. oceanica meadows in the Ligurian Sea have undergone a documented regression in the last century due to increasing anthropogenic pressures along the coast, and are therefore an ideal subject for a study of diachronic mapping. The longest available data series concerning a P. oceanica meadow is that of the Bergeggi meadow. From the 1980s to the present, 15 different maps depicting the biocoenosis present in the Marine Protected Area seabed have been collated and compared. Maps show different degrees of reliability depending on the scale, the data acquisition method and positioning system. The diachronic analysis shows two distinct phases: between 1987 and 2005 there is a decrease in the surface area of P. oceanica, while in the last 15 years the extension of the Bergeggi meadow does not seem to show any significant change but a partial recovery locally. This result could be ascribed to regional conservation initiatives, including the establishment of the Marine Protected Area in 2007, and is consistent with the trend of P. oceanica meadows at the Mediterranean scale, whose regression seems to have stopped in recent years.